2013
DOI: 10.1371/journal.pone.0073037
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence and Relative Risk of Stroke among Patients with Bipolar Disorder: A Seven-Year Follow-Up Study

Abstract: ObjectiveThis study aimed to estimate the incidence and relative risk of stroke and post-stroke all-cause mortality among patients with bipolar disorder.MethodsThis study identified a study population from the National Health Insurance Research Database (NHIRD) between 1999 and 2003 that included 16,821 patients with bipolar disorder and 67,284 age- and sex-matched control participants without bipolar disorder. The participants who had experienced a stroke between 1999 and 2003 were excluded and were randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 40 publications
2
20
1
Order By: Relevance
“…Our findings that age, male gender, diabetes mellitus, and hypertension are associated with an increased risk of stroke in patients with bipolar disorder were compatible with two previous studies similarly focusing on patients with bipolar disorder (2,3). Of note, our finding that female gender was associated with a reduced risk of stroke was consistent with these two studies but the underlying mechanism is not well understood.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings that age, male gender, diabetes mellitus, and hypertension are associated with an increased risk of stroke in patients with bipolar disorder were compatible with two previous studies similarly focusing on patients with bipolar disorder (2,3). Of note, our finding that female gender was associated with a reduced risk of stroke was consistent with these two studies but the underlying mechanism is not well understood.…”
Section: Discussionsupporting
confidence: 92%
“…Stroke is one of the most severe medical conditions and it has been reported to account for 5.5 million deaths and 44 million disability‐adjusted life‐years lost worldwide annually . Previous studies have demonstrated an increased risk of stroke of up to twofold among patients with bipolar disorder . However, the possible effects of medication on the risk of stroke were not further analyzed in these studies.…”
mentioning
confidence: 98%
“… 10 , 21 However, studies specifically targeting the link between bipolar disorder and young stroke were lacking. Wu et al 22 reported that bipolar patients with stroke were younger than those without stroke, although the stroke event still occurred at a mean age over 45 years. 22 Another large-scale study showing the link between bipolar disorder and stroke (prevalence ratio 3.14, CI = 2.42∼4.06) had 46% of its bipolar group younger than age 40 (1873/4067 patients), but no stratified data were available.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al 22 reported that bipolar patients with stroke were younger than those without stroke, although the stroke event still occurred at a mean age over 45 years. 22 Another large-scale study showing the link between bipolar disorder and stroke (prevalence ratio 3.14, CI = 2.42∼4.06) had 46% of its bipolar group younger than age 40 (1873/4067 patients), but no stratified data were available. 23 In our study, model 1 adjusting for demographic data and medical comorbidities, but not model 2 with an additional adjustment with other psychiatric comorbidities, showed a significant relationship between bipolar disorder and young ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…While there is consistent evidence showing the high prevalence of comorbid medical conditions in BD768, 769, 770, 771, 772, 773, 774 and the negative impact these diagnoses have on longevity,775, 776 these conditions frequently go undiagnosed or undertreated. In a large UK cross‐sectional analysis of electronic data sets involving 1.7 million patients in primary care, those diagnosed with BD, when compared with healthy controls, had lower rates of diagnoses (odds ratio [OR] 0.59, 95% confidence interval [CI] 0.54‐0.63) and treatment of medical conditions, despite higher rates of one (OR 1.2, 95% CI 1.16‐1.39) or multiple illnesses (OR 1.44, 95% CI 1.3‐1.64) 769…”
Section: Specific Populationsmentioning
confidence: 99%